KEMAMPUAN MENGHAFAL AL-QUR’AN DENGAN METODE KAISA DALAM PERSPEKTIF MULTIPLE INTELLIGENCE - umi salamah (stit-islamic-village, 2019)
Technological developments bring a lot of impact to the community without the exception of children, from gadgets, games, music, movies, and so on. This makes children reluctant to learn the science of religion, especially the Qur'an. Al-Qur'an as a way of life for Muslims, must be studied, and applied in life. The purpose of this study is to determine the ability to memorize the Qur'an using the Kaisa method in the perspective of multiple intelligence. The Kaisa method is a way of memorizing the Koran which is oriented to memorization and understanding of the verses of the Koran along with their meanings through movements or kinesthetic which are adapted to the meaning of each verse so as to make it easy to understand and remember every verse of the Qur'an given . This research was conducted at RTQ Malang City. This research method is descriptive qualitative, data collection is through observation, interviews, and documentation. The results of the study found that memorizing the Qur'an using the Kaisa method was able to increase the interest of children in memorizing the Qur'an, understanding the meaning, and accommodating multiple intelligences (multiple intelligence)